Assessment of Argentinean Patagonia pollution: PBDEs, OCPs and PCBs in different matrices from the Río Negro basin - Miglioranza, Karina Silvia Beatriz (2013)
This work reports the occurrence and distribution of organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs) in soil, sediment, suspended particle matter (SPM), streamwater and macrophytes, along the Río Negro basin, Argentinean Patagonia. The clear predominance of OCPs among all matrices indicates the impact of agriculture on the watershed. The highest levels were found for pp'-DDE which represented up to 95% in agricultural soils (42.0-1.27x10 3 ng/g d.w) from the Upper Valley (upstream), where long and historical intensive fruit cultures have been settled and represent a hot spot of legacy pesticides for the environment. The insecticide endosulfan, currently in use, was also found in all matrices. Levels ranged between 0.3 and 708.0ng/g d.w, being the highest concentrations those of SPM from the Middle Valley, just before the delta area, where pesticides would be retained leading to lower concentrations as was observed downstream. PCB (#153, 138, 110, 101) and PBDE (BDE-47) levels were directly related with the presence of hydroelectric power plants, dams and dumping sites, mainly settled in the Upper Valley (0.8ng/g and 15.1ng/g d.w for PBDEs and PCBs, respectively). Although there was a decreasing gradient of these pollutant concentrations through the river flow, downstream urban areas enhanced PCB concentrations in the aquatic environment. More efforts and monitoring programs are highly required to control and reduce soil erosion in order to prevent the availability of forbidden pollutants in the environment.